Making Translation Testing More Teaching-oriented: A Case Study of Translation Testing in China - Li, Defeng (Meta, 2006)
AbstractDespite the fact that translation teaching research has been gaining momentum over the last two decades, little has been written and therefore known about translation assessment in the teaching context. This article reports on a data-based empirical study of translation testing in China. The issues raised in it range from teachers’ attitudes towards testing to its objectives, design, contents, frequency, and its pedagogical roles. It is suggested that more research be done on translation testing, of which the first task is to develop a theoretical framework to provide guidance for translation testing practice and research. It is further recommended that translation testing be made more teaching-oriented and brought closer to the real world of professional translation.